Perangkat Lunak Keamanan Informasi Pada Mobile Menggunakan Metode Stream Dan Generator Cipher - Mohamad Ridwan, Asep Budiman Kusdinar , (PROCEEDING IC-ITECHS 2014, 2014)
Integration method of  stream and generator cipher can used to randomizing  messageinformation. Delivery of message information through email or mobile is required a good security and safety system. So can protect message information that be acceptable by receiver carefully and  precise.  In  this  article  methodologies  which  will  be  applied  for randomize message  information  is    processing  encryption  and    descryption  to    apply  stream  and generator cipher. The software of  this can be used to send message information applicable to information in character secret by using key stream and   generator cipher as introduction lock  of  message information.  So  with  existence  of  this  stream  and  generator  cipher  is locking authentication message information become safe and is well ensured.